A new species of Anisophya (Orthoptera: Tettigoniidae: Phaneropterinae) from Argentina, its ultrasound male-female communication, life history and ecology - Delaloye, Michelle; Braun, Holger (Zootaxa, 2023)
Anisophya arreguii sp. nov. is added as third species of the genus in Buenos Aires Province. A population living in humid meadows near La Plata, regularly observed during the last five years, was found to be different from A. punctinervis. It appears in two distinct annual generations. The male produces a continuous ultrasound calling song, to which the female responds with short signals after particular syllables. The verification of all Anisophya observations from Argentina on iNaturalist helped clarifying the distinctiveness of the new species. Some ecological aspects are briefly discussed, such as a vulnerable population in the city of La Plata.